[PP.29.31] ORTHOSTATIC HYPOTENSION AND RISK OF INCIDENT DEMENTIA. (September 2017) - Cremer, A.; Soumaré, A.; Berr, C.; Dartigues, J.F.; Gabelle, A.; Tzourio, C.
Abstract : Objective: Several studies indicate a potential link between orthostatic hypotension (OH) and incident dementia, but without substantial evidence to date. Objective: to study the association between OH and dementia in a cohort of elderly individuals. Figure. No caption available. Design and method: Baseline lying and standing blood pressure measurements were taken from 7425 subjects in the 3C study. These subjects were then followed-up over 12 years. Cox proportional hazard models, adjusted for potential confounders, were used to estimate the risk of incident dementia according to OH status. Sensitivity analysis was performed using the so-called illness-death model, a specific statistical method. Results: OH frequency was found to be around 13%, and 760 cases of dementia were diagnosed during follow-up. We observed significant association between the presence of OH at baseline and the occurrence of dementia during the follow-up, with an increased risk of at least 25% observed regardless of the OH threshold and the statistical method used. Conclusions: There is an association between OH and dementia. Considering that OH is a common condition and is easy to measure, OH measurements could help to identify subjects with higher risk of dementia. Moreover, reducing OH could be a step to prevent conversion to dementia.